The Head and Neck Squamous Cell Carcinoma Microenvironment as a Potential Target for Cancer Therapy - Plzák, Jan (Cancers (Basel), 2019)
Similarly to other types of malignant tumours, the incidence of head and neck cancer is increasing globally. It is frequently associated with smoking and alcohol abuse, and in a broader sense also with prolonged exposure to these factors during ageing. A higher incidence of tumours observed in younger populations without a history of alcohol and tobacco abuse may be due to HPV infection. Malignant tumours form an intricate ecosystem of cancer cells, fibroblasts, blood/lymphatic capillaries and infiltrating immune cells. This dynamic system, the tumour microenvironment, has a significant impact on the biological properties of cancer cells. The microenvironment participates in the control of local aggressiveness of cancer cells, their growth, and their consequent migration to lymph nodes and distant organs during metastatic spread. In cancers originating from squamous epithelium, a similarity was demonstrated between the cancer microenvironment and healing wounds. In this review, we focus on the specificity of the microenvironment of head and neck cancer with emphasis on the mechanism of intercellular crosstalk manipulation for potential therapeutic application.